The Impact of Peer Influence and Service Quality on Insurance Product Purchase Decisions - Made Sri Laksmi; Wayan Bagia; Nana Trianasari (Universitas Pendidikan Ganesha, 2022)
Insurance is insurance or agreement between two parties, the first party is required to pay contributions or premiums while the second party is required to provide guarantees to the first party if something bad happens to the insured participant or object. In addition to the community, insurance is also used by companies as a step to make investments to minimize losses that may occur in the future. This indicates that insurance has become an important part for every company. This study aims to empirically examine the role of peer influence and service quality on purchasing decisions of insurance products. The research method used is causal quantitative because the data used are quantitative data and the research variables have a causal relationship. The analytical tool used to test the hypothesis is to use Structural Equation Modeling (SEM). SEM analysis is used because SEM has the ability to measure latent variables that are not directly measured but through the estimation of indicators or parameters. The results show that peer influence and service quality have an effect either partially or simultaneously on purchasing decisions. This means that in order to increase sales of insurance products, it is important for management to pay close attention to the variables of peer influence and service quality.